Castor oil based polyurethane adhesive content on OSSB produced with soybean straw - Silva, João Vítor Felippe; Silva, Maria Fernanda Felippe; Ferreira, Bruno Santos; Fiorelli, Juliano; Christoforo, André Luis; Campos, Cristiane Inácio de (Ambiente Construído, 2020)
Oriented Structural Straw Board (OSSB) panels are composites made from straw originally from agricultural residues and non-formaldehyde based adhesive, whose main application is for construction as a closing and ceiling material. The objective of this study was to evaluate the effect of the polyurethane adhesive content on physical and mechanical properties of OSSB produced with locally available SbS (soybean straw). Four castor oil based polyurethane ratios (6%, 9%, 12% and 15%, by mass of the SbS) were tested. OSSB was evaluated according to European standards for wood-based composites; also, a physical and chemical characterization of the SbS was performed. SbS has an irregular shape, which reduced the OSSB mechanical performance due to the low densification of the composite and the development of transversal cracks on the SbS after the OSSB manufacturing process. The static bending and thickness swelling performance of SbS OSSB was not improved by the increase of polyurethane adhesive content. SbS low ash content and neutral pH extractives indicates that probably its chemical properties should not affect the setting of the adhesive.